Similar Metabolic, Innate Immunity, and Adipokine Profiles in Adult and Pediatric Sepsis Versus Systemic Inflammatory Response Syndrome—A Pilot Study. Issue 11 (November 2017) - Tavladaki, Theonymfi; Spanaki, Anna Maria; Dimitriou, Helen; Kondili, Efmorfia; Choulaki, Christianna; Georgopoulos, Dimitris; Briassoulis, George
Abstract : Objectives: To examine whether the septic profiles of heat shock protein 72, heat shock protein 90α, resistin, adiponectin, oxygen consumption, CO2 production, energy expenditure, and metabolic pattern, along with illness severity, nutritional, and inflammatory indices, differ between adult and pediatric patients compared with systemic inflammatory response syndrome and healthy controls. To evaluate whether these biomolecules may discriminate sepsis from systemic inflammatory response syndrome in adult and pediatric patients. Design: Prospective cohort study. Setting: University ICU and PICU. Patients: Seventy-eight adults (sepsis/23; systemic inflammatory response syndrome/23; healthy controls/33), 67 children (sepsis/18; systemic inflammatory response syndrome/23; controls/27), mechanically ventilated. Interventions: None. Measurements and Main Results: Flow cytometry determined mean fluorescence intensity for monocyte or neutrophil heat shock protein expression. Resistin, adiponectin, and extracellular heat shock proteins were measured using enzyme-linked immunosorbent assay; energy expenditure by E-COVX (GE Healthcare). Genomic DNA was extracted with PureLink Genomic DNA kit (Invitrogen, Carlsbad, CA) to detect heat shock protein 72 single nucleotide polymorphisms. Similarly, in adult and pediatric patients, Acute Physiology and Chronic Evaluation-II/Acute Physiology and Pediatric Risk of Mortality-III, Simplified Acute Physiology Score-III, C -reactive protein, lactate, and resistin were higher and myocardial contractility, monocyte heat shock protein 72, oxygen consumption, CO2 production, energy expenditure, metabolic pattern, glucose, and albumin lower in sepsis compared with systemic inflammatory response syndrome or controls ( p < 0.05). For discriminating sepsis from systemic inflammatory response syndrome, resistin, extracellular heat shock protein 90α, and lactate achieved a receiver operating characteristic curve greater than 0.80 in children and greater than 0.75 in adults ( p < 0.05). In both, adults and children, genotype heat shock protein 72 analysis did not disclose any diagnosis or mortality group differences regarding either rs6457452 or rs1061581 haplotypes. Conclusions: Sepsis presents with similar profiles in adult and pediatric patients, characterized by enhanced inflammatory hormonal response and by repressed innate immunity, metabolism, and myocardial contractility. These features early distinguish sepsis from systemic inflammatory response syndrome across all age groups. Abstract : Supplemental Digital Content is available in the text.